(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the impact of tax reforms on India’s economic growth, focusing on key developments in the tax system since independence. Tax reform in India has undergone significant transformations, especially since the economic liberalization in the early 1990s. The introduction of various reforms, particularly the Goods and Services Tax (GST) in 2017 and reductions in corporate tax rates, has aimed to create a more efficient, transparent, and equitable tax structure. These reforms have not only sought to enhance revenue collection but also to stimulate investment, boost consumption, and promote economic activity across various sectors. The analysis reveals that tax reforms have played a crucial role in enhancing the ease of doing business, fostering a competitive environment, and attracting foreign direct investment (FDI). The reduction in corporate tax rates, for instance, has incentivized both domestic and foreign companies to invest in India, thereby contributing to job creation and industrial growth. Additionally, the simplification of the tax regime through GST has eliminated cascading taxes, improved compliance, and facilitated the movement of goods and services across the country.However, the impact of tax reforms has not been uniform across sectors, with certain industries benefiting more than others. The paper also highlights the importance of complementary policies, such as infrastructure development and social welfare programs, to maximize the benefits of tax reforms. Ultimately, this study underscores the critical role of tax reforms in shaping India’s economic landscape, emphasizing the need for ongoing adjustments to ensure sustainable and inclusive growth in the context of a rapidly changing global economy. Through continuous reforms and adaptations, India can harness its tax system to support long-term economic development and address socio-economic disparities effectively.